Resident reflections on resident-patient communication during family medicine clinic visits. Issue 3 (March 2020) - Turner, Jeanine Warisse; Robinson, James; Morris, Elise; Oberkircher, Katherine; Rios, Rebeca; Roett, Michelle
Highlights: Residents focus feedback on rapport and relationship building skills. Residents perceive navigating the appointment as a critical skill. Residents view communication as transmitting information rather than a dialogue. Private blogs can offer an opportunity for resident feedback and support. Abstract: Objective: Residency programs emphasize effective doctor and patient interaction. However, training can be time intensive and logistically challenging. This paper examines a blog providing resident peer feedback and an opportunity to explore how residents think about patient communication. Methods: A grounded theory approach examined peer commenting on doctor patient interactions. Between 2012–2015, at a U.S. East Coast Family Medicine Clinic, 35 family medicine residents were recorded interacting with patients, producing a total of 84 videos which were posted to a blog. Residents reflected on these videos resulting in 356 responses, 3162 meaning units and 211 codes. Codes were grouped into 10 themes. Further analysis explored how residents signaled positive and negative doctor communications-related behavior. Results: Most common themes identified were Rapport/Relationship building skills, Negotiating the appointment, and Peer interaction. Most common themes discussed in light of both positive and negative behavior were Education, Use of technology, and Negotiating the appointment. Conclusions: Residents view their communication with patients as more of a transmission of critical information than an opportunity for dialogue. Practice implications: Findings support how online tools can be used for resident reflections. These tools can reveal resident perceptions of salient communication information in a clinical encounter.